(untitled) (Quinto Sol, 2017)
Introduction to the conferences by Dr. Ana María Lorandi and Dr. Jorge Pinto Rodríguez, within the framework of the II CIPIAL - International Congress of Indigenous Peoples of Latin America (held in Santa Rosa, September 2016)